2005
DOI: 10.1503/cmaj.050406
|View full text |Cite
|
Sign up to set email alerts
|

Adverse perinatal outcomes associated with homelessness and substance use in pregnancy

Abstract: Hilarity and good humour … help enormously in both the study and the practice of medicine … [I]t is an unpardonable sin to go about among patients with a long face.-William OslerYes, that's right, it's already time to send us your creative contributions for CMAJ's Holiday Review 2005. We're looking for humour, spoofs, personal reflections, history of medicine, off-beat scientific explorations and postcards from the edge of medicine.Send your offerings through our online manuscript tracking system (http://mc.ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
58
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 17 publications
5
58
0
3
Order By: Relevance
“…In this study, homelessness modified the effect of maternal pregnancy practices and outcomes, as well as stressful and abusive life events on infant birth weight. The overall lower infant birth weight and preterm birth among homeless women as compared with non-homeless women was also reported in a Canadian prospective cohort study by Little et al [16]. The modifying impact of homelessness on adverse maternal health and infant birth weight in our study may have been due to the severity of adverse health circumstances reported by homeless women, such as vaginal bleeding, kidney disease, and nausea.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In this study, homelessness modified the effect of maternal pregnancy practices and outcomes, as well as stressful and abusive life events on infant birth weight. The overall lower infant birth weight and preterm birth among homeless women as compared with non-homeless women was also reported in a Canadian prospective cohort study by Little et al [16]. The modifying impact of homelessness on adverse maternal health and infant birth weight in our study may have been due to the severity of adverse health circumstances reported by homeless women, such as vaginal bleeding, kidney disease, and nausea.…”
Section: Discussionsupporting
confidence: 86%
“…Hence, such pregnancy-related outcomes are linked to stress and abuse experienced by the mother. Research has shown adverse birth outcomes related to homelessness, including low birth weight and premature infants, which are strong risk factors for infant mortality and developmental disabilities [14][15][16]. However, to our knowledge, no study has considered the modifying effect of homelessness on the relationship between maternal psychological stress and physical abuse and infant birth weight.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that women who self-reported as being homeless during their pregnancy were more likely to have low-birth-weight infants and premature infants. [3][4][5] Infants born weighing less than 2500 g, and infants born at less than 37 weeks gestational age, suffer some of the highest rates of neonatal and infant death in the United States. 6,7 The factors contributing to poorer birth outcomes and increased IMR in homeless women are complex and vary based on the community.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…Maternal homelessness the year prior to delivery was associated with a 69 g mean decrease in birth weight, a higher prevalence of low (1500-2,500 g) and very low (\1,500 g) birth weight, but no difference in gestational age, when compared to infants of housed women. Little et al [13] reported both lower infant birth weight and a nearly threefold increased risk for preterm births in 3,895 Canadian women, homeless or ''underhoused'' (not further defined) during pregnancy. Homeless women are more likely than housed women to report violence exposure, substance use, low educational level, obesity or underweight, and chronic physical and mental health conditions [14][15][16][17]-all potentially compounded by decreased access to health care services [18].…”
Section: Introductionmentioning
confidence: 99%